2010
DOI: 10.1073/pnas.0910929107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine receptor Tim-4 is essential for the maintenance of the homeostatic state of resident peritoneal macrophages

Abstract: Tim-4 is a phosphatidylserine (PS) receptor that is expressed on various macrophage subsets. It mediates phagocytosis of apoptotic cells by peritoneal macrophages. The in vivo functions of Tim-4 in phagocytosis and immune responses, however, are still unclear. In this study, we show that Tim-4 quickly forms punctate caps on contact with apoptotic cells, in contrast to its normal diffused expression on the surface of phagocytes. Despite its expression in marginal zone and tingible body macrophages, Tim-4 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 25 publications
6
139
0
Order By: Relevance
“…Thus, our data support a scenario in which PS exposure on ACs serves as a crucial "eat me" signal and likewise triggers anti-inflammatory signaling cascades within the MF that alter its phenotype (28,29). Indeed, exposure of PS is essential for the anti-inflammatory effects of ACs (30,31); and during the last several years several PS-binding receptors, such as Tim4 and MerTK, were identified and shown to mediate the nonimmunogenic clearance of ACs (19,20,24,(32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, our data support a scenario in which PS exposure on ACs serves as a crucial "eat me" signal and likewise triggers anti-inflammatory signaling cascades within the MF that alter its phenotype (28,29). Indeed, exposure of PS is essential for the anti-inflammatory effects of ACs (30,31); and during the last several years several PS-binding receptors, such as Tim4 and MerTK, were identified and shown to mediate the nonimmunogenic clearance of ACs (19,20,24,(32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 76%
“…To better understand the underlying molecular mechanisms, we studied the phagocytosis of ACs by inflammatory and resident MFs of the peritoneal cavity. By using Tim4 as a specific marker for resident peritoneal MFs (19,20), we were able to distinguish the two populations of MFs during flow cytometry and via immunofluorescence (Fig. 1A, 1B).…”
Section: Tissue-resident Mfs Perform the Noninflammatory Clearance Ofmentioning
confidence: 99%
“…34,57 In contrast to TIM-3, which is expressed on multiple immune and non-immune cells, TIM-4 expression is restricted to APCs such as DCs and macrophages. 58 Recent analysis of TIM-4-deficient mice has shown that TIM-4 dampens inflammatory responses and maintains immune tolerance, implying that TIM-4 may have a potential role in the regulation of immune responses in the tumor microenvironment 59,60 ( Figure 2). The role of TIM-4 in tumor immunosurveillance, and in particular the regulation of antitumor immune responses and inflammation-associated carcinogenesis, remains obscure.…”
Section: Tim-4mentioning
confidence: 99%
“…PS recognition receptors can either bind PS directly or bind indirectly through soluble bridging molecules. Receptors that directly interact with PS include members of the TIM (T cell immunoglobulin domain and mucin domain) family (43)(44)(45)(46)(47)(48)(49), BAI1, the seven transmembrane brain angiogenesis inhibitor 1 (50), and the atypical EGF-motif containing membrane protein Stabilin-2 (20). MFG-E8 has been identified as a bridging molecule that can simultaneously bind PS on apoptotic cells with high affinity (51)(52)(53)(54) and engage integrin v 3 on phagocytes.…”
Section: Phosphatidylserine On Apoptotic Cells Mediates Immunosuppresmentioning
confidence: 99%